Event-Based H Consensus Control of Multi-Agent Systems With Relative Output Feedback: The Finite-Horizon Case - Liu, Qinyuan; Wang, Zidong; He, Xiao; Zhou, D. H. (IEEE transactions on automatic control, 2015)
In this technical note, the H ∞ consensus control problem is investigated over a finite horizon for general discrete time-varying multi-agent systems subject to energy-bounded external disturbances. A decentralized estimation-based output feedback control protocol is put forward via the relative output measurements. A novel event-based mechanism is proposed for each intelligent agent to utilize the available information in order to decide when to broadcast messages and update control input. The aim of the problem addressed is to co-design the time-varying controller and estimator parameters such that the controlled multi-agent systems achieve consensus with a disturbance attenuation level γ over a finite horizon [0, T]. A constrained recursive Riccati difference equation approach is developed to derive the sufficient conditions under which the H ∞ consensus performance is guaranteed in the framework of event-based scheme. Furthermore, the desired controller and estimator parameters can be iteratively computed by resorting to the Moore-Penrose pseudo inverse. Finally, the effectiveness of the developed event-based H∞ consensus control strategy is demonstrated in the numerical simulation.